Promoting successful transition to adulthood for students with disabilities - Morgan, Robert L.; Riesen, Timothy J. (What works for special-needs learners, 2016)
"Comprehensively addressing the challenges of transition, this book provides practical knowledge and tools geared toward real-world educators. It presents clear guidelines for all aspects of team-based transition planning for individuals with various levels of disability, illustrated with vignettes of three secondary students who are followed throughout the book. The authors describe evidence-based practices for conducting assessments and promoting optimal outcomes in the areas of employment, postsecondary education, and independent living. Keys to family involvement, self-determination, interagency collaboration, and problem solving are highlighted. Several reproducible forms can be downloaded and printed in a convenient 8 1/2" x 11" size"--Provided by publisher.